Internationalizing Teaching, Localizing Learning : An Examination of English Language Teaching Reforms and English Use in China - McPherron, Paul (Language and Globalization, 2017)
Based on ethnographic and policy data collected over a ten-year span at a university in the People's Republic of China, this book analyses the history of English Language Teaching (ELT) polices in Chinese higher education. The book uses the university as a lens in which to investigate the creative imaginations and divergent (re)appropriations of teaching methods, learning materials, and language use in the Chinese ELT context. Book chapters move beyond mere descriptions of tensions and point to the local understandings and practices of English teachers (both local and foreign) and students. Working together, these teachers and students are constantly articulating new social and political conditions and meanings outside and inside given discourses and traditions of ELT. The book's main argument is that these multiple stakeholders must be given a more prominent role in shaping policy and curriculum at universities and other English language contexts around the world.- Resumé vydavatel